(untitled) (Global Journal of Human-Social Science, 2019)
This study was undertaken to assess the contribution of the rural poor people to environmental degradation in Annang nation of Akwa Ibom State Related literature was reviewed on sex religion marital status family size and age Five hypotheses were formulated for the study Stratified random sampling technique was used to select one thousand five hundred respondents for the study The instrument for the data collection was 25 item questionnaires on Rural Poverty and Environmental Degradation SUQRURED Data from one thousand five hundred completed questionnaires were used to analysis Hypotheses were tested using the independent t-test The result indicated that the contributions of the rural poor people toward environmental degradation do not differ by their family sizes and age Recommendations were made towards quality protection of the environment from degradation